2007
DOI: 10.1080/01676830601174585
|View full text |Cite
|
Sign up to set email alerts
|

Inferior Oblique Schwannoma: Diagnosis and Management

Abstract: This rare case highlights that schwannoma may occur in association with the inferior oblique complex and we suggest that schwannomas should now be considered in the differential diagnosis when patients present with a clinically-suspected or radiologically-proven orbital mass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 5 publications
0
3
1
Order By: Relevance
“…6 Schwannoma typically grows slowly, with proptosis progressing over the course of years. It is associated with neurofibromatosis type 2, 7 although there were no signs of neurofibromatosis in our patient. When considering schwannoma as a diagnosis, compatible CT features include a well-demarcated hypo-or isodense homogenous lesion with no bony invasion or muscle infiltration and the presence of bony remodeling.…”
Section: T a G G E D H 1 Referencest A G G E D Econtrasting
confidence: 52%
“…6 Schwannoma typically grows slowly, with proptosis progressing over the course of years. It is associated with neurofibromatosis type 2, 7 although there were no signs of neurofibromatosis in our patient. When considering schwannoma as a diagnosis, compatible CT features include a well-demarcated hypo-or isodense homogenous lesion with no bony invasion or muscle infiltration and the presence of bony remodeling.…”
Section: T a G G E D H 1 Referencest A G G E D Econtrasting
confidence: 52%
“…Recently, several authors have reported cases of endoscopic coblation-assisted surgery in juvenile angiofibroma; however, clinical studies considering endoscopic harmonic scalpel-assisted surgery for vascular tumors of the anterior skull base are still lacking. 5 In that regard, we have been using the harmonic scalpel in our endoscopic skull base practice since 2008, with promising results. This has reduced the duration of surgical procedures by significantly reducing the amount of intraoperative bleeding, thus allowing for a more straightforward procedure and facilitation of dissection of tissues and planes.…”
Section: Discussionmentioning
confidence: 99%
“…Presenting symptoms of this pathology are nonspecific and depend greatly on the localization of the tumor within the orbit, but nonpulsatile ocular proptosis and displacement of the globe are frequent. Schwannomas are encapsulated, meaning they do not infiltrate adjacent structures 5. Any optic nerve or extraocular muscle involvement is therefore because of the direct compression of the structure or its vasculature 1,6.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation